2021
DOI: 10.4103/jfmpc.jfmpc_71_21
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of uropathogens and antibiotic sensitivity in diabetes patients attending to out – Patient department and diabetes clinic of a teaching hospital

Abstract: Introduction: Diabetes mellitus is the most common endocrinological disease associated with different life-threatening infections. Urinary Tract Infection is one of them which may lead to Intensive care Unit admission and even death. In this study, we would like to find out the spectrum of uropathogen and its antibiotic sensitivity, so that we can choose empirical antibiotics early to save lives. Aim and Objectives: To find out spectrum of uropathogens in Diabetic patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…The results of antibiotic susceptibility pattern from Otukpo revealed E. coli to be moderately susceptible to streptomycin 60%, cefotaxime 55% and imipenem 50% while at the same time showing moderate to high resistance to cotrimoxazole 50%, tetracycline 55%, ceftriaxone 60%, ciprofloxacin 65%, ofloxacin 70%, nalidixic acid 70%, levofloxacin 80%, aztreonam 80%, ampicillin 80%. This was contrary to a study in India [36] who reported complete sensitivity (100%) to imipenem but comparable resistant pattern has been observed in Ethiopia to nalidixic acid 70% and cotrimoxazole 64.7% [26].…”
Section: Discussioncontrasting
confidence: 99%
“…The results of antibiotic susceptibility pattern from Otukpo revealed E. coli to be moderately susceptible to streptomycin 60%, cefotaxime 55% and imipenem 50% while at the same time showing moderate to high resistance to cotrimoxazole 50%, tetracycline 55%, ceftriaxone 60%, ciprofloxacin 65%, ofloxacin 70%, nalidixic acid 70%, levofloxacin 80%, aztreonam 80%, ampicillin 80%. This was contrary to a study in India [36] who reported complete sensitivity (100%) to imipenem but comparable resistant pattern has been observed in Ethiopia to nalidixic acid 70% and cotrimoxazole 64.7% [26].…”
Section: Discussioncontrasting
confidence: 99%
“…16 study from Nath, et al found that there is an increase of antibiotic drug resistance associated with oral formulations, especially fluoroquinolones and Ampicillin, used in OPD cases. 17 Our results echo similar findings of Nath, et al and found an increase in drug resistance, largely to fluoroquinolones and cephalosporins. Our results coincide with other studies, as we isolated similar common uropathogens including E.coli (60%), Klebsiellaspp (18.6%) and Pseudomonasspp (14%).…”
Section: Discussionsupporting
confidence: 92%
“…Studies at Banjarmasin represent Escherichia coli (65.3%) and Pseudomonas aeruginosa (11.5%) as the majority etiology (20). This result is similar to another study in Kalyani, India, that shows the most common bacteria in diabetic patients with UTI is Escherichia coli (38.77%) (12). jurnal.umj.ac.id/index.php/MMJ mmjfkk@umj.ac.id e-issn: 2721-317X Muhammadiyah Medical Journal Nitrofurantoin susceptibility testing towards Escherichia coli is that five isolates are sensitive, five are intermediate, and two are resistant.…”
Section: Discussionsupporting
confidence: 85%
“…Drug-resistant UTIs are emerging in community and healthcare setups (12). Some studies reported the effects of drug resistance are deaths, length of hospitalization, and healthcare costs (13).…”
Section: Introductionmentioning
confidence: 99%